This preview shows pages 1–2. Sign up to view the full content.
This preview has intentionally blurred sections. Sign up to view the full version.
View Full Document
Unformatted text preview: Math 23b Homework 4 Solutions 1. Let Q ( n ) be the statement P ( n ), so that Q ( n ) is true if and only if P ( n ) is false. We will prove that Q ( n ) is true for all n N by induction. Since P (1) is false, Q (1) is true. Now suppose Q ( n ) is true for some n . Then P ( n ) is false, so by assumption P ( n + 1) is also false, and hence Q ( n + 1) is true. Thus, by induction, Q ( n ) is true for all n , so P ( n ) is false for all n N . 2. We will prove the statement P ( n ) : n i =1 i ( i + 1) = n ( n +1)( n +2) 3 for all n N , by induction. For n = 1, we have 1 i =1 i ( i + 1) = 1(1 + 1) = 1(1+1)(1+2) 3 . Now suppose n i =1 i ( i + 1) = n ( n +1)( n +2) 3 . Then n +1 i =1 i ( i +1) = n i =1 i ( i +1)+( n +1)( n +2) = n ( n +1)( n +2) 3 + 3( n +1)( n +2) 3 = ( n +1)( n +2)( n +3) 3 . Thus, by induction, P ( n ) is true for all n N . 3. Let a i R . We will prove the statement P ( n ) :  n i =1 a i  n i =1  a i  for all n...
View Full
Document
 Spring '09
 BongLian
 Math

Click to edit the document details